STUDY ON FREE VIBRATION ANALYSIS FOR HONEYCOMB SANDWICH STRUCTURE WITH DOUBLE CORES - LU Xiang; YANG JiuYue; WANG RuiPeng; QIAN RuoLi (Jixie qiangdu)
The free vibration problem of the honeycomb sandwich structure with double cores was studied based on the Layerwise/Solid-Elements（ LW/SE） and Fixed-interface Modal Synthesis Technique（ FMST） of the dynamic substructure method. The governing equation and the total modal space of the honeycomb sandwich structure were assembled based on LW/SE and FMST,respectively,and the final governing equation on the basis of the modal spaces was assembled based on the governing equation and the total modal space. This method obtains the natural frequency of the honeycomb sandwich structure with double cores accurately and reduces memory requirement. The numerical results of the method are compared with those obtained by the 3D solid finite element,and good agreements are achieved.